2020
DOI: 10.17305/bjbms.2020.4620
|View full text |Cite
|
Sign up to set email alerts
|

P2X7R as an independent prognostic indicator in gastric cancer

Abstract: Gastric cancer is one of the foremost causes of cancer related death around the world. The P2X7 receptor (P2X7R), a member of the P2X receptor subfamily of P2 receptors, is a unique molecule that has been shown to affect tumor growth and progression as well as various inflammatory processes, including proliferation of T lymphocytes, release of cytokines, and production of free oxygen radicals. P2X7R has been established as a prognostic parameter in some cancers and, recently, it has been investigated in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…While nfP2X7 was identified in the human HT-29 and Colo-205 colon cancer cell lines (Barden et al, 2009), other reports have shown P2X7 expression in human HCT8, Caco-2, Colo-205, and murine MCA38 colon cancer cell lines and the latter cell line was found to possess functional P2X7 macropore (Coutinho-Silva et al, 2005;Kunzli et al, 2011;Bian et al, 2013). Analysis of P2X7 expression in 156 gastric cancers corelated P2X7 expression with tumor burden and poor survival suggesting that P2X7 may be involved in the progression of gastric cancer (Calik et al, 2020).…”
Section: Colorectal and Gastric Cancermentioning
confidence: 88%
See 1 more Smart Citation
“…While nfP2X7 was identified in the human HT-29 and Colo-205 colon cancer cell lines (Barden et al, 2009), other reports have shown P2X7 expression in human HCT8, Caco-2, Colo-205, and murine MCA38 colon cancer cell lines and the latter cell line was found to possess functional P2X7 macropore (Coutinho-Silva et al, 2005;Kunzli et al, 2011;Bian et al, 2013). Analysis of P2X7 expression in 156 gastric cancers corelated P2X7 expression with tumor burden and poor survival suggesting that P2X7 may be involved in the progression of gastric cancer (Calik et al, 2020).…”
Section: Colorectal and Gastric Cancermentioning
confidence: 88%
“…Prostate (Slater et al, 2004a;Maianski et al, 2007;Adinolfi et al, 2009;Barden et al, 2009;Ravenna et al, 2009;Adinolfi et al, 2010;Barden et al, 2014;Ghalali et al, 2014;Qiu et al, 2014;Solini et al, 2015;Barden et al, 2016;Gilbert et al, 2019) Lung (Barden et al, 2009;Takai et al, 2012;Jelassi et al, 2013;Barden et al, 2014;Takai et al, 2014;Schmid et al, 2015;Gilbert et al, 2019) Kidney (Liu et al, 2015;Gilbert et al, 2019) Colorectal (Coutinho-Silva et al, 2005;Barden et al, 2009;Li et al, 2009;Kunzli et al, 2011;Bian et al, 2013;Barden et al, 2014;Barden et al, 2016;Qian et al, 2017;Gilbert et al, 2019;) Gastric (Barden et al, 2009;Barden et al, 2014;Calik et al, 2020) Breast (Slater et al, 2004b;Barden et al, 2009;Li et al, 2009;Tafani et al, 2010;Jelassi et al, 2011;Huang et al, 2013;Jelassi et al, 2013;Barden et al, 2014;Chadet et al, 2014;<...>…”
Section: Cancer Typeunclassified
“…In this study, we screened eight P2 receptors which were commonly reported in cancer—the vast majority of these studies relate to P2X7, P2Y2 and P2Y12 receptors ( Adinolfi et al, 2012 ; Li et al, 2013 ; Chadet et al, 2014 ; Jin et al, 2014 ). P2X7 receptors have been shown to express strongly in prostate cancer cells, in osteosarcoma, in lymphocyte-infiltrating gastric cancer, pancreatic ductal adenocarcinoma cell lines, and in patients with malignant pleural mesothelioma, and its antagonism has been shown to inhibit growth of tumors in various in vivo models ( Qiu et al, 2014 ; Giannuzzo et al, 2015 ; Amoroso et al, 2016 ; Zhang et al, 2019 ; Calik et al, 2020 ). We found this true in the case of IMR-32 neuroblastoma and MCF-7 breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an antibody directed against nfP2X7 also proved efficacious in reducing basal cell carcinoma growth in a phase I clinical trial on humans [83]. These data are of sure relevance to develop new P2X7-targeting therapies, also considering that an increasing number of studies report an association between P2X7 overexpression and bad prognosis or response to therapy in oncologic patients [42,65,72,[84][85][86][87]. The majority of these studies do not take into account known P2X7 variants, but some interesting progress was made in this field of research in last years that we cover in the present overview.…”
Section: Role Of Atp and P2x7 Receptor In Oncologymentioning
confidence: 95%